A combination of aramid nanofiber and silver nanoparticle decorated boron nitride for the preparation of a composite film with superior thermally conductive performance. Issue 4 (3rd April 2022) - Zhao, Lihua; Liao, Changjun; Liu, Yang; Huang, Xiaolong; Ning, Wenjun; Wang, Zhong; Jia, Lichuan; Ren, Junwen
ABSTRACT: The developments in the high-power densities and high integration of electronic devices have put forward higher requirements for advanced thermal management materials (TMMs) to meet the rising demand for heat dissipation. However, it has remained a major challenge to achieve significant enhancement of thermal conductivity (TC) of TMMs without compromising their mechanical and dielectric properties. Here, we report a flexible, thermally conductive composite film that contain aramid nanofiber (ANF) and silver nanoparticles (AgNPs) decorated with boron nitride (BN), the in-plane TC of which is up to 12 W/mK at 40 wt.% filler contents. Such a high TC is attributed to the bridging role of AgNPs, which greatly reduces the interfacial thermal resistance of composites. At the same time, the as-prepared composite films possess outstanding mechanical strength (>126 MPa), owing to the coupling between the ANF network and the favourable hydrogen bonding interaction between the ANF and the functional BN. Moreover, a low dielectric loss (<0.05), high electrical resistivity ( 10 14 Ω·cm), and high decomposition temperature (>500°C) are simultaneously achieved for the composite films. These findings offer a facile strategy for the design of multifunctional TMMs, which hold great promising for application in electric devices. Graphical Abstract: uf0001